Improved Display of Hepatic Arterial Anatomy Using Differential Subsampling With Cartesian Ordering (DISCO) With Gadoxetic Acid‐Enhanced MRI: Comparison With Single Arterial Phase MRI and Computed Tomographic Angiography. Issue 6 (13th December 2019) - Wei, Yi; Chen, Guoyong; Tang, Hehan; Yuan, Yuan; Huang, Zixing; He, Xiaopeng; Ye, Zheng; Zhang, Tong; Wei, Xiaocheng; Song, Bin
Abstract : Background: In clinical practice arterial anatomy evaluation is often determined using computed tomographic angiography (CTA); the effect of enhanced MRI has been neglected. Purpose: To evaluate whether multiple arterial phase (MAP) images from patients who underwent differential subsampling with Cartesian ordering (DISCO) acquisition would improve the hepatic arterial display compared with single arterial phase (SAP) and CTA. Study Type: A prospective, randomized trial. Subjects: In all, 130 patients (mean age, 55.81 ± 9.43 years; range, 35–78 years) including 89 men and 41 women. Field Strength/Sequence: 3.0T, DISCO, liver acquisition with volume acceleration‐flexible (LAVA‐Flex), CTA. Assessment: A simple randomization was conducted and the study was subdivided into study part I (DISCO vs. SAP) and study part II (DISCO vs. CTA). Ten hepatic arterial segments were independently evaluated by three readers in the axial plane and the quality of hepatic arterial display was assessed using a four‐point scale. Statistical Tests: Kendall's W‐test, χ 2 test, Mann–Whitney U ‐test, and Kruskal–Wallis one‐way analysis of variance (ANOVA) test. Results: Excellent interobserver agreement was obtained for hepatic arterial display (all Kendall's W values >0.80). For study part I, the mean arterial display scores for the common hepatic artery (CHA), proper hepatic artery (PHA), left hepatic artery (LHA), right hepatic artery (RHA), left gastric artery (LGA), and gastroduodenal artery (GDA) obtained with DISCO were higher than that obtained with SAP imaging (all P  < 0.01). For study part II, comparable image quality for CHA ( P = 0.798), PHA ( P = 0.440), LHA ( P = 0.211), RHA ( P = 0.775) LGA ( P = 0.468), and GDA ( P = 0.801) was obtained with DISCO and CTA. Data Conclusion: The use of MAP acquisition with DISCO is superior to the use of SAP in hepatic arterial display and compares favorably with CTA; in the future, DISCO possibly can replace the latter ionization‐related method to provide a more comprehensive evaluation of the liver arterial vessels. Level of Evidence: 1 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2020;51:1766–1776.